Improvements in functional exercise performance at 6 months following bariatric surgery: A prospective cohort study - Gorek Dilektasli, Asli; Coşkun, Funda; Karadag, Mehmet; Dilektasli, Evren (The European Research Journal, 2025)
Objectives: Successful weight loss after bariatric surgery has been associated with a variety of improvements in health status. Delayed heart rate recovery after the six-minute walking test (6MWT) is associated with morbidity and mortality in various cardiac and respiratory diseases. We aimed to evaluate the effect of bariatric surgery on functional exercise performance and autonomic dysfunction in patients who had undergone laparoscopic sleeve gastrectomy. Methods: Pre-operative and post-operative (6 months) demographics, comorbidities, weight, and height of the patients undergoing laparoscopic sleeve gastrectomy were recorded. All patients underwent a 6MWT. 6MWT was performed according to the American Thoracic Society standards. Additionally, heart rate (HR) and oxygen saturation were assessed at rest, at the end of the test, and in the first minute following testing. Autonomic dysfunction was assessed by heart rate recovery (HRR), which was calculated as the difference between the maximum HR reached during the 6MWT and the HR at the first minute after the test. Patients were classified depending on whether their HRR was slow (HRR